Motivasi dan Kemampuan Penalaran Matematis Siswa dengan Pembelajaran Kooperatif Tipe Pair Check Disertai Reward Pada Materi Fungsi - Eliza, Rivdya; Khadijah, Khadijah; Wulandari, Utari (Universitas Islam Negeri Imam Bonjol Padang, 2018)
The purpose of this study is 1) To know the motivation to learn mathematics of taught by using cooperative learning model type Pair Check with reward higher than student motivation taught by convensional learning,and 2) To know the mathematical reasoning ability which was taught by using cooperative learning model type Pair Check with reward on material function is higher than students mathematical reasoning ability taught by convensional learning. This type of research is Quasi Experimental Research with Randomized Control Group Only Design. The population in this study is all eighth grade student of SMPN 19 Padang. In obtaining the sample class it is need to be done normality, homogeneity and equality of classroom average tests the class selected as the experimental class is VIII.5 class and the control class is VIII.3. The result of the research shows that 1) learning motivation of students which was taught by using cooperative learning Pair Check model with Reward is higher than student’s motivation taught by convensional learning. Hypothesis test that is t-score (7.034) > t-table (1.67), 2) students' mathematical reasoning ability after being taught by cooperative model type Pair Check with reward is higher than the students' mathematical reasoning abilities taught by conventional learning models. Seen from the average score of the experimental class test score of 80.16 and the average of the control class test score of 74.13. After hypothesis testing using t-test, obtained tscore > t-table (1.867 > 1.67) at 95%. So it can be student mathematical reasoning ability of class VIII SMPN 19 Padang which is taught by cooperative learning model type Pair Check with reward is higher than taught by using conventional learning.Keywords: Mathematic Reasoning Ability And Student Motivation, Model Cooperative Type Pair Check, Reward Fungsi, And Mathematic